Fun-Defense: Games that Teach Fundamental Martial-Arts and Build Self-Esteem. - Damon Leiss; Paul Luebbers (The Advocate, 2013)
Associations have been made among having a low self-esteem and both being a bully and being bullied. With bullying and its victimization being a common problem in today’s schools, increasing students’ self-esteem could benefit schools with this dilemma. Learning martial arts has been shown to increase students’ self-esteem. However, training in martial arts can take considerable time, usually more time than can be allotted in a typical middle school physical education unit. This paper provides teachers a way to increase students’ self-esteem and confidence by quickly teaching and reinforcing fundamental martial arts skills through a game series known as “Fun-Defense.”